2010
DOI: 10.1088/1751-8113/43/29/293001
|View full text |Cite
|
Sign up to set email alerts
|

n-ary algebras: a review with applications

Abstract: Abstract. This paper reviews the properties and applications of certain n-ary generalizations of Lie algebras in a self-contained and unified way. These generalizations are algebraic structures in which the two entries Lie bracket has been replaced by a bracket with n entries. Each type of n-ary bracket satisfies a specific characteristic identity which plays the rôle of the Jacobi identity for Lie algebras. Particular attention will be paid to generalized Lie algebras, which are defined by even multibrackets … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
209
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(211 citation statements)
references
References 363 publications
(1,361 reference statements)
0
209
0
1
Order By: Relevance
“…Let us mention here that we will not actually use 3-algebra notation, and will instead follow [15] in writing down expressions adapted to SDiff(M n ). Another paper which treats SDiff gauge theory is the review [26], where 3-algebra expressions can be found.…”
Section: The Sdiff(s 3 ) Nambu-chern-simons Lagrangian Harmonic Expamentioning
confidence: 99%
“…Let us mention here that we will not actually use 3-algebra notation, and will instead follow [15] in writing down expressions adapted to SDiff(M n ). Another paper which treats SDiff gauge theory is the review [26], where 3-algebra expressions can be found.…”
Section: The Sdiff(s 3 ) Nambu-chern-simons Lagrangian Harmonic Expamentioning
confidence: 99%
“…Later there has been an increasing interest of developing the various -ary generalization of Lie algebra and their applications in -body mechanics, quantum physics, geometry; mathematical genetics and etc. A detailed survey on -ary generalizations of Lie algebras and their applications in physics have been given by de Azcárraga and Izquierdo [1].…”
Section: Theoremmentioning
confidence: 99%
“…the class of algebras are satisfied of all identities of A. For a commutator and a Jordan (symmetrized) product, we use the following standard notation [ ] = − • = + Let A be an arbitrary -ary algebra over F with -ary multiplication 1 ∈ A. We will denote by…”
Section: Introductionmentioning
confidence: 99%
“…induces an action of the multiplicative R. Remark 6.4. As the Grassmann algebra A(E * ) can be understood as the algebra of smooth functions on the graded manifold E [1] (an N-manifold of degree 1 in the terminology ofŠevera and Roytenberg [86,87]), following [97,98] we can view the de Rham derivative d Π as a vector field of degree 1 on E [1]. This vector field is homological, (d Π ) 2 = 0, if and only if we are actually dealing with a Lie algebroid.…”
Section: Graded Manifoldsmentioning
confidence: 99%